FAKTOR-FAKTOR KEJADIAN IKTERUS NEONATUS DI RSUD PANGERAN JAYA SUMITRA KABUPATEN KOTABARU - Abdan, Rusdiyana; Hasanah, Siti Noor (LPPM Universitas Sari Mulia, 2024)
Background: Neonatal jaundice in newborns is a problem that often appears in neonates. Neonatal jaundice is a yellow discoloration of a baby's skin, conjunctiva, and sclera as a result of increased levels of bilirubin in the blood that causes jaundice and death in infants. Preliminary study of the incidence of jaundice at Prince Jaya Sumitra Kotabaru Hospital in 2021 was 15 (2.08%) out of 719 total baby births and in 2022 there were 30 (3.02%) who experienced neonatal jaundice from 992 births of hospitalized patients. Objective:.Knowing the factors of neonatal jaundice at Prince Jaya Sumitra Hospital, Kotabaru Regency in 2022. Methods: Type of quantitative research with case control design. The study samples were 30 case groups and 30 control groups. Random sampling technique. Statistical test using chi square. Result: Statistical analysis obtained the p value of each variable, namely gestational age (0.001), type of delivery (0.000), infection (0.233) and birth weight (0.001) which means there is a relationship between gestational age, type of delivery and birth weight variables with the incidence of neonatal jaundice, while the infection variable has no relationship with the incidence of neonatal jaundice. Conclusion: Factors associated with the incidence of jaundice are gestational age, type of delivery and birth weight. Keywords: Gestational Age, Neonatal Jaundice, Type of Delivery, Weight